2020
DOI: 10.1101/2020.11.25.396259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupal cannibalism by worker honey bees contributes to the spread of Deformed wing virus

Abstract: Transmission routes impact pathogen virulence and genetics, therefore comprehensive knowledge of these routes and their contribution to pathogen circulation is essential for understanding host-pathogen interactions and designing control strategies. Deformed wing virus (DWV), a principal viral pathogen of honey bees associated with increased honey bee mortality and colony losses, became highly virulent with the spread of its vector, the ectoparasitic mite Varroa destructor. Reproduction of Varroa mites occurs i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The persistence of DWV‐B in the absence of the vector illustrates the importance of alternative transmission modes. DWV is transmissible in pollen and larval food (Singh et al., 2010; Yue & Genersch, 2005), and acquired through the cannibalisation of infected pupae (Posada‐Florez et al., 2021). Transovum vertical transmission from queen to offspring can occur, but is not the most efficient transmission pathway (Amiri et al., 2018; Chen, Pettis, et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of DWV‐B in the absence of the vector illustrates the importance of alternative transmission modes. DWV is transmissible in pollen and larval food (Singh et al., 2010; Yue & Genersch, 2005), and acquired through the cannibalisation of infected pupae (Posada‐Florez et al., 2021). Transovum vertical transmission from queen to offspring can occur, but is not the most efficient transmission pathway (Amiri et al., 2018; Chen, Pettis, et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One study [96] found that removal above 95% of freeze-killed pupae lowered mite population growth and significantly lowered DWV titres in workers than colonies below 95% removal. However, cannibalism of infested pupae allows DWV prevalence to remain high [97] even in resistant populations [98], but titres fall since oral (natural) viral transmission is much less infective than via injection [93,97].…”
Section: (C) Colony-level Effectsmentioning
confidence: 99%
“…However, risks are also associated with cannibalism. The predation of conspecifics is a pathway for spreading pathogens and diseases, especially species‐specific ones (Khodaei & Long, 2020; Pfennig et al., 1998; Posada‐Florez et al., 2021). The cannibals can increase the risk of injury by preying on individuals with similar abilities (Khodaei & Long, 2020).…”
Section: Introductionmentioning
confidence: 99%